If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + x = 36 Solving 18 + x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + x = 36 + -18 Combine like terms: 18 + -18 = 0 0 + x = 36 + -18 x = 36 + -18 Combine like terms: 36 + -18 = 18 x = 18 Simplifying x = 18
| x^3+3x^2=88x | | x-3/2=x+4/2 | | 26=y+10-3g | | b^2-8b-7=0 | | W=x+cuzfory | | -8+x=2x+1 | | -2y=15 | | [x]=2014 | | 0.21y-1.8=0.11+1-0.6y | | x(3x+4)=4 | | 14x=17x-14 | | 38=2-3(y-5) | | 6(r-3)-5r=-11+3 | | 3x+2y=-13 | | 2p^2-9p-18= | | 6w=-8 | | 888= | | -8=3y-3y-5y | | 15.8=10x | | 2t^2+8t-21=0 | | 9p^2-12p+4= | | 5z-27=11+3z | | -27=5x-12 | | -27-4=5 | | -27-4= | | 6(r-3)-5=5r-11+3 | | 2500y=500000 | | 2500=500000 | | -36-x-4x=64 | | 8p^2-19p+9= | | (x-2/3)(5x+4)=0 | | 60=-12a |